"At times avuncular and cantankerous, with the reflexes of a mongoose": Understanding Self-Expression through Augmentative and Alternative Communication Devices - Kane, Shaun; Morris, Meredith Ringel; Paradiso, Ann; Campbell, Jon (Proceedings of CSCW 2017, 2017)
Amyotrophic Lateral Sclerosis (ALS) is a disease that causes individuals to lose their ability to control their muscles, eventually leaving them unable to speak or write. People with ALS often transition to using an augmentative and alternative communication device (AAC), which requires both the AAC user and their conversation partners to adjust to new and different communication patterns. We conducted interviews with seven individuals with ALS and their partners, focusing on how AAC use has impacted their communication and personal expression. Our participants experienced a range of communication difficulties, including conversational pacing, personality expression, and interacting with unfamiliar conversational partners. Participants worked to adapt their communication behaviors to the AAC device, but still experienced challenges in expressing themselves, and sometimes felt compelled to withdraw from social interaction. By improving our understanding of how people transition to using AAC, we may inform improved designs for future AAC devices.